Hazardous Aspects of Urea Hydrogen Peroxide Adduct - Matyáš, Robert; Šelešovský, Jakub; Pelikán, Vojtěch; Szala, Mateusz; Cudzilo, Stanislaw; Trzcinski, Waldemar A.; Gozin, Michael (Wiley-VCH, 2017)
The adduct of urea and hydrogen peroxide (UHP) is industrially produced material on a large scale. Although UHP is widely used as a bleaching and oxidizing agent, its properties as hazardous energetic material are generally overlooked. In this work we report comprehensive characterization of UHP thermal and explosive properties, and describe results of a series of tests typically used for evaluation of explosives. We found that UHP is a compound with a negative value of standard enthalpy of formation (-565.1 kJ·mol-1). It is not sensitive to impact and friction. However, we demonstrated that as-manufactured UHP (ρ = 0.93 g·cm-3; packed into a steel pipe with inner diameter of 206 mm) could be a detonable material with experimental velocity of detonation (VOD) of 3,600 m·s-1. Moreover, for UHP with maximal theoretical density (ρ = 1.43 g·cm-3), the calculated VOD reaches 5,219 m·s-1. Based on our findings, we recommend that present regulations regarding the handling, storage and transportation of the UHP should be revised, especially in cases where UHP is kept on a large scale, under confinement and at places where the temperature can reach above 60 ºC.
Rizikové aspekty aduktu močoviny s peroxidem vodíku
Keywords: urea hydrogen peroxide; peroxohydrate; detonability; detonation velocity; thermal stability; Peroxid močoviny; detonace; detonační rychlost; termická stabilita